Toxicity and Antimicrobial Activities of L. (Amaranthaceae) Harvested From Formulated Soils at Different Growth Stages - Muhali Olaide Jimoh PhD; Anthony Jide Afolayan PhD; Francis Bayo Lewu PhD (SAGE Publishing, 2020)
This study examined the toxicity and antimicrobial effects of ethanol and aqueous extracts from Amaranthus caudatus grown on soils formulated from parent particles of silt, sand and clay in a glasshouse. Four different soils namely; sandy clay loam, loam, clayey loam and silty clay loam from were formulated were used for cultivation with the unfractionated soil which was the control. Crude extracts obtained from the plant shoots harvested at different growth stages were tested on some certain gram-negative and gram-positive bacteria and some fungi via agar dilution assay. The toxicity of the water and ethanol extracts was also examined via Artemia salina assay and the level of lethality was measured against Clarkson's lethality scale. All aqueous samples, as well as ethanol extracts of flowering and pre-flowering harvests of control soil tested, were non-toxic (LC 50 > 1 mg/mL). At post flowering, the ethanolic extracts were highly toxic mostly in clayey loam, control, sandy-clayey loam soils (LC 50 < 0.5 mg/mL). Also, antifungal effects of the plant revealed that extracts inhibited the growth of Candida albicans significantly with mild effect on Candida glabrata , Penicillium chrysogenum and Penicillium aurantiogriseum suggesting that the plant is a promising pharmacological candidate in the treatment of candidiasis. For an optimal yield of non-toxic supplement for household consumption which may also serve as pharmacological precursors, clayey loam soil is recommended for cultivation and harvesting may occur at pre-flowering or flowering stage using ethanol and water as solvents of extraction.